Pasar rasulan sebagai ekosistem ekonomi kegiatan budaya desa: Perputaran uang, modal sosial, dan tata kelola berkelanjutan di Semanu, Gunungkidul - Fetria Eka Yudiana; Heri Kurniawan (Journal of Economics Research and Policy Studies, 2026)
Rasulan in Gunungkidul is commonly understood as a village thanksgiving tradition, yet its economic role has not been sufficiently examined. This study revises the reading of Rasulan from a cultural ceremony into a temporary village-event economy, here conceptualized as Pasar Rasulan. Data were collected through semi-structured interviews, observation, and event-related documents, then analyzed using thematic analysis. The findings show that Rasulan generates multiple channels of local economic circulation. The organizer's budget exceeded Rp60 million; identified rental spending reached Rp24.55 million; parking revenue was at least Rp6.5 million; committee consumption spending reached Rp7.5 million; and documented average vendor revenues varied across food vendors, toy sellers, snack sellers, and other micro-traders. Household spending during the main day also created local demand through food preparation and guest hosting. Beyond these transactions, social capital shaped coordination, access to selling opportunities, and the community's ability to mobilize assets such as land, labor, and trust. The study contributes by mapping the micro-mechanisms of a village cultural event and showing that sustainable governance, transparent record-keeping, local procurement, vendor arrangements, and waste management are required if Rasulan is to become a more accountable instrument of community-based local economic strengthening.